Re-Understanding Banjhakri: Forest Shaman as a Therapeutic Ally and a Social Equalizer - Paudel, Uttam (Nepalese Culture, 2025)
This article explores the social and therapeutic roles of banjhakri, a supernatural shamanic entity whose presence extends from West Central Nepal to parts of North Eastern India. It draws exclusively upon a rich cross section of extant scholarship to offer a composite assessment of folklores and symbolism surrounding banjhakri. As such, the article discusses his physical and behavioural attributes, his status as the root guru of shamans, and his symbiotic relationship with his consort and antagonist, banjhakrini. In addition, I examine the curious phenomenon of abduction of mainly young boys by banjhakri, which marks their initiation into this arcane world. Moreover, I analyze banjhakri's role as a therapeutic ally, a social equalizer, and a tool that allows shamans to interpret woes and maladies. The article concludes by positing that banjhakri’s place in Nepalese society has been tied inextricably to his utility in Nepalese social life, and discusses his legacy amidst unprecedented changes in social dynamics.